Anti-inflammatory dietary supplements in prevention of diseases in geriatric people - Singh, Amrandra Prasad (International Journal of Advances in Medicine, 2019)
As our age advances, many changes are seen in our body, such as cellular changes, cardiovascular problems, cerebrovascular diseases, including cancer mediated by inflammation and their mediators such as free radicals (ROS, RNS), cytokines, transcription factors (NF-KB, STAT3) due to altered dietary patterns and digestive disorders. The disease pattern can be suppressed by including anti-inflammatory dietary supplements in our diet to prevent various diseases in geriatric peoples associated with inflammation. Chronic activation of the inflammatory response, defined as inflammation, is the key physio-pathological substrate for anabolic resistance, sarcopenia and frailty in older individuals. Nutrients can theoretically modulate this phenomenon. This article briefs about anti-inflammatory dietary supplements in prevention of diseases associated with inflammation in geriatric people.